MEMS vibratory gyroscopes structural approaches to improve robustness - Acar, Cenk. (Springer US, 2009)
MEMS Vibratory Gyroscopes provides a solid foundation in the theory and fundamental operational principles of micromachined vibratory rate gyroscopes, and introduces structural designs that provide inherent robustness against structural and environmental variations. In part one, the dynamics of the vibratory gyroscope sensing element is developed, common micro-fabrication processes and methods commonly used in inertial sensor production are summarized, design of mechanical structures for both linear and torsional gyroscopes are presented, and electrical actuation and detection methods are discussed along with details on experimental characterization of MEMS gyroscopes. In part two, design concepts that improve robustness of the micromachined sensing element are introduced, supported by constructive computational examples and experimental results illustrating the material. MEMS Vibratory Gyroscopes is a must have book for engineers in both industry and academia who specialize in the design and manufacture of gyroscopes. Readers will find: A unique balance between theory and practical design issues. Comprehensive and detailed information outlining the mathematical models of the mechanical structure and system-level sensor design. Solid background Information on mechanical and electrical design, fabrication, packaging, testing and characterization. About The MEMs Reference Shelf: "The MEMs Reference Shelf is a series devoted to Micro-Electro-Mechanical Systems (MEMs) which combine mechanical, electrical, optical, or fluidic elements on a common microfabricated substrate to create sensors, actuators, and microsystems. The series, authored by leading MEMs practitioners, strives to provide a framework where basic principles, known methodologies and new applications are integrated in a coherent and consistent manner." STEPHEN D. SENTURIA Massachusetts Institute of Technology, Professor of Electrical Engineering, Emeritus. Fundamentals of Micromachined Vibratory Gyroscopes -- Fundamentals of Micromachined Gyroscopes -- Fabrication Technologies -- Mechanical Design of MEMS Gyroscopes -- Electrical Design of MEMS Gyroscopes -- Structural Approaches to Improve Robustness -- Linear Multi DOF Architecture -- Torsional Multi DOF Architecture -- Distributed Mass Architecture -- Conclusions and Future Trends.